The Bankruptcy Of Airlines As Lessee In Finance Leasing Based On Cape Town Convention 2001 And Harmonization With The Bankruptcy And Suspension Of Payment Act Number 37 Years 2004 - Hijriya, Shafira (UI Scholars Hub, 2017)
By the development of the airlines industry in Indonesia today, international lease finance from all around the world (lessor) puthigher trustto airline business in Indonesia. In reality many airlines company (lessee) is bankrupt, because of the inability to pay his debt to the lessor. Based on the Irrevocable Deregistration and Export Request Authorization (IDERA) in the Cape Town Convention, if the airlines company had been bankrupt and could not pay the debt of finance leasing, the aircrafts must bereturned to the finance leasing. In contrary, there is disparities with Bankruptcy and Suspension of Payments Act No.7/2004 in Indonesia, so we need to harmonize the regulation between Bankruptcy Law and Leasing Rule in Indonesia with International Regulation to create the legal certainty to both companies